Investigation of microbiological quality of dietary supplement products - Patipong, Tanutcha; Tatsawong, Naritsara; Meksuwan, Jarunee; Panthipamporn, Theera; Sapoo, Nopamart (Bulletin of Applied Sciences, 2023)
This research aimed to study the microbiological quality of commercially available dietary supplement products. The contamination of three pathogenic bacteria, Salmonella spp., Staphylococcus aureus and Clostridium spp., as well as an indicator of unhygienic manufacturing process, Escherichia coli, were investigated. The results showed that a total of 33 products did not contain Salmonella spp. S. aureus and E. coli. However, five products contaminated with Clostridium spp. were found. The contamination indicated the distribution of dietary supplement products which do not meet the microbiological standard according to Ministry of Public Health and Food and Drug Administration. These products may be the cause of adverse impacts to customer health.